My granny went to market : a round-the-world counting rhyme - Blackstone, Stella; Corr, Christopher (Cambridge, Mass. : Barefoot Books, 2006)
A child's grandmother travels around the world, buying things in quantities that illustrate counting from one to ten.
Keywords: Voyages and travels -- Juvenile fiction; Grandmothers -- Juvenile fiction; Counting -- Juvenile fiction; Stories in rhyme